Substrates and cover crop residues on the suppression of sclerotia and carpogenic germination of Sclerotinia sclerotiorum - Monteiro, Fernando Pereira; Pacheco, Leandro Pereira; Lorenzetti, Emi Rainildes; Armesto, Cecília; de Souza, Paulo Estevão; de Abreu, Mário Sobral (Comunicata Scientiae, 2012)
<!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:SimSun; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} > <! [endif] > <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 200%; background: none repeat scroll 0% 0% white;" _mce_style="margin-bottom: 0.0001pt; text-align: justify; line-height: 200%; background: none repeat scroll 0% 0% white;">Cover crops influence the populations of microorganisms such a pathogen. In this work the objective was to evaluate the influence of different cover crops on the rate recovering sclerotia of Sclerotinia sclerotiorum in soil as well as the mycelial growth rate for recovered sclerotia. We also evaluated the influence of different substrates for carpogenic germination. The cover crops used in the experiment were Crotalaria juncea L., Urochloa ruziziensis R. Germ. & Evrard, Panicum maximum cv. Mombaça Jacq., Pennisetum glaucum (L.) R. Brown, Cajanus cajan (L.) Millsp.) e Stylosantes capitata Vog.; Stylosanthes macrocephala Ferr. Et Costa). The substrates used for carpogenic germination were agar-water, agar- water + filter paper, sand and mixed sand and soil. The cover crops showed efficiency in the suppression of S. sclerotiorum, especially for Stylosanthes spp. and Panicum maximum cv. Mombaça in the rate recovering of sclerotia and for Stylosanthes spp. in the rate of mycelial growth by providing a suitable environment for growth of antagonistic organisms. For the number of carpogenic germinated sclerotia and for the number of apothecia formed on different substrates, the sand; and the agar-water and soil + sand mixture stood out, respectively.<--> Cover crops influence populations of microorganisms, such as a pathogen. In this work the objectivewas to evaluate the influence of different cover crops on the sclerotia of Sclerotinia sclerotiorumrecovering rate in soil as well as the mycelial growth rate for recovered sclerotia. The influence ofdifferent substrates for carpogenic germination was also evaluated. The cover crops used in theexperiment were Crotalaria juncea L., Urochloa ruziziensis R. Germ. & Evrard, Panicum maximumcv. Mombaça Jacq., Pennisetum glaucum (L.) R. Brown, Cajanus cajan (L.) Millsp.) and Stylosantescapitata Vog.; Stylosanthes macrocephala Ferr. Et Costa). The substrates used for carpogenicgermination were agar-water, agar- water + filter paper, sand and mixed sand and soil. The covercrops showed efficiency in the suppression of S. sclerotiorum, especially for Stylosanthes spp. andPanicum maximum cv. Mombaça in the rate recovering of sclerotia and for Stylosanthes spp.in the rate of mycelial growth by providing a suitable environment for growth of antagonisticmicroorganisms. As for the number of carpogenic germinated sclerotia and for the number ofapothecia formed on different substrates, the sand; agar-water and soil + sand mixture stood out,respectively. Substratos e resíduos de plantas de cobertura na supressão dos escleródios egerminação carpogênica de Sclerotinia sclerotiorum As plantas de cobertura influenciam as populações de microrganismos, tal como o fitopatógeno.Neste trabalho o objetivo foi avaliar a influência de diferentes plantas de cobertura sobre ataxa de recuperação dos escleródios de Sclerotinia sclerotiorum no solo, bem como o índiceda velocidade de crescimento micelial para os escleródios recuperados. Avaliou-se tambéma influência de diferentes substratos para germinação carpogênica. As plantas de coberturautilizadas no experimento foram Crotalaria juncea L., Urochloa ruziziensis R. Germ. & Evrard, Panicummaximum cv. Mombaça Jacq., Pennisetum glaucum (L.) R. Brown, Cajanus cajan (L.) Millsp.) eStylosantes capitata Vog.; Stylosanthes macrocephala Ferr. Et Costa). Os substratos utilizados paraa germinação carpogênica foram ágar-água, ágar-água+papel filtro, areia e mistura areia e solo.As plantas de cobertura apresentaram eficiência na supressão de S. sclerotiorum, com destaque,para Stylosantes spp. e Panicum maximum cv. Mombaça quanto à taxa de recuperação deescleródios e para o Stylosantes spp. quanto ao índice da velocidade de crescimento micelial,por proporcionar ambiente adequado ao crescimento de organismos antagonistas. Quanto aonúmero de escleródios germinados carpogenicamente e ao número de apotécios formados emdiferentes substratos, destacaram-se a areia; e o ágar e mistura solo+areia, respectivamente.